The Value of Selected Ecosystem Services: A Case Study of East Mau Forest Ecosystem, Kenya - Langat, D.K; Maranga, E.K; Aboud, A.A; Cheboiwo, J.K (Journal of Forests, 2018)
The ecosystem services from Kenya’s forest ecosystems have remained largely unmeasured and undervalued. Consequently, the benefits they provide are ignored in most forest management and conservation decisions. This has led to degradation and conversion to alternative uses. To provide a sound basis for decision making in forest management, it is important to estimate economic values provided by East Mau. This study relied on data collected from households using structured interviews and secondary data from published and unpublished sources. The total indirect use values (soil functions, hydrological functions, climate regulation values) from East Mau forest ecosystem was about US219 million (KES 20billion). The economic values of nutrient cycling, erosion control, water flow and quality regulation were US13.30, US 4.50 ha-1yr-1, US 1421.03 ha-1yr-1 and US 12.83 HH-1yr-1 respectively. The annual value for carbon sequestration and oxygen generation was US3308.05 ha-1yr-1 and 1365.13 ha-1yr-1 respectively. These results provide valuable information on the magnitude of the selected ecosystem services that could be relevant in decision-making concerning conservation and management of East Mau forest ecosystem for enhanced ecosystem services and livelihoods.